(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Western culture has disfigured the body of the will and imposed organs on the body and an alienated and fascist life, Artaud (1999) and Deleuze and Guattari (1997) expose. Such notions of the body are close to the authorial dance. Setenta (2008), Rocha (2016), and Lepecki (2017) problematize a practice for an Uncommon body. These references guide a look at the dance experienced by the Guido Viaro group, intending to find clues for a clinic and a critique, where dance is thinking, writing, moving. Accompanied by three lines of cartography, the research process deals with: i) an expanded Body without Organs?; ii) dance practices for Unusual bodies; and iii) five verbs for an affective and reflective observation with the dance.